Evaluasi Manajemen Central Sterille Suply Departement (CSSD) dalam Meminimalisir Terjadinya Healthcare Associated Infectiomn (HAIs) di RSDU Dr. Darsono Pacitan - Ahmad Ahid Mudayana; Niska Yustiana (Jurnal Kesehatan, 2017)
Central Sterile Supply Department (CSSD) or Sterilization Center Installation is a strategic service unit in preventing infection. And has the main function of preparing clean and sterile tools for the purposes of patient care at the hospital. The research method used descriptive qualitative and research design used case study. Techniques of collecting data using interviews, checklist and document review. The results show that 1) CSSD planning is well planned, 2) CSSD organizing has not been fully structured, 3) Implementation consists of receiving tools, packaging, labeling, sterilization, distribution, and storage, 4) supervision done every 6 months.